Calibration and accuracy analysis of robotic belt grinding system using the ruby probe and criteria sphere. (June 2018) - Xu, Xiaohu; Zhu, Dahu; Wang, Jinshan; Yan, Sijie; Ding, Han
Highlights: The sphere-to-sphere method replacing the traditional point-to-point method is introduced to calibrate the robotic belt grinding system. The position of the origin point of grinding machine frame is found to significantly affect the robotic belt grinding effects. Compared with the plunge grinding style, better machined surface quality can be guaranteed by using the longitudinal grinding style. Experiments on the robotic belt grinding of the aero-engine blade validate the practicability of the improved calibration method. Abstract: Calibration in the robotic belt grinding of complex blades is considered as one of the key bottlenecks of measurement accuracy. To enhance the accuracy of robotic calibration system, an improved method is proposed in this paper to calibrate the tool (grinding machine) frame and workpiece (aero-engine blade) frame by holding the ruby probe as the main calibration tool. Firstly, the sphere-to-sphere method replacing the traditional point-to-point method is put forward to calibrate the flexible and fixed probe frame. Secondly, the calibrated flexible and fixed probe frame is employed to precisely seek the origin point of tool frame and then to calibrate it accurately. Thirdly, both the rough calibration (manual calibration) and fine calibration (auto calibration) are adopted to calibrate the workpiece frame, the resulting translation and rotation errors are controlled at small values to improve the calibration accuracy. Finally, a typical case on robotic belt grinding of aero-engine blade is conducted to validate the calibration results of the robotic belt grinding system (RBGS).